The Relationship between the age of the pregnant mother and the values hemoglobin blood and packed cell volume (PCV) in the Third Trimester for different age groups (descriptive study) - وفاء جاسم سلمان (College of Education for Women, 2019)
Pregnancy pose an additional burden on the body of the mother so as to meet their needs and the needs of the fetus and the body's need to iron increases excessively during pregnancy and iron is an essential element for the formation of hemoglobin blood Either hemoglobin is the key ingredient for red blood cells which carries oxygen to parts of the body, alas, most of the pregnant women begin their pregnancy inadequate stocks of iron in their bodies, which does not cover their need and requirement of the fetus, especially in the second and third trimesters of pregnancy When you reach the mother to the period in which they did not have the adequate amount of iron to produce hemoglobin become the mother was anemic So emerged the problem of research to figure out the relationship between maternal age and hemoglobin values packed cell volume in the last third of pregnancy and the results showed that the second age group (Class of childbearing age ) showed best values of hemoglobin in the blood and also showed that the average size of the packed cell volume within the normal range , reaching ( 30.6 %) for the first age group as well as the presence of a statistically significant relationship among the values of hemoglobin and the size of tpacked cell volume he with three age groups and show a statistically significant relationship between the age of the mother and the values of hemoglobin in the blood and the high incidence of anemia among sample